PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL PEMEDIASI PADA BADAN PERTANAHAN NASIONAL (BPN) TANGGAMUS, LAMPUNG - Ristian Lilis; Tasya Monica; Rudi Stiawan; Vicky F Sanjaya (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
The purpose of this study was to examine the effect of leadership style on employeeperformance and to examine organizational culture as the influence betweenleadership style and employee performance. This study used a descriptivequantitative method by taking a sample of 55 employees who were collected usinga questionnaire with a 5-point Likert scale. The data analysis used was a structuralequation model with the partial least square (PLS-SEM) method using the smartPLSapplication. The results showed that the Leadership Style was able to improveemployee performance directly or indirectly, namely through enhancingorganizational culture and having an impact on improving employee performance.